2016
DOI: 10.13102/sociobiology.v63i1.739
|View full text |Cite
|
Sign up to set email alerts
|

Apitoxin harvest affects population development but not the hygienic behavior of African-derived honey bees

Abstract: Apitoxin harvest affects population development but not the hygienic behavior of African-derived honey bees IntroductionApitoxin is a product that bees can offer to humans, the word originating from the Latin apis (bee) and toxikon (venom.) This substance is produced by the acid glands of worker bees, and characterized as being clear, colorless, and highly soluble in water (Cruz-Landim & Abdalla, 2002).Apitoxin toxicity is attributed to three proteic components: enzymes (phospholipase A2 and hyaluronidase), la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Thus, this study shows that this practice has a negative effect on the development of the gland, even considering that the period during which the colonies was stressed was short (1 h per month) this is in accordance with results reported by Modanesi et al (2015). Onari et al (2016) showed that the apitoxin harvest impairs the population development of the colonies, also evidencing the negative effects of this management.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, this study shows that this practice has a negative effect on the development of the gland, even considering that the period during which the colonies was stressed was short (1 h per month) this is in accordance with results reported by Modanesi et al (2015). Onari et al (2016) showed that the apitoxin harvest impairs the population development of the colonies, also evidencing the negative effects of this management.…”
Section: Discussionsupporting
confidence: 92%